Coherent interface strengthening of ultrahigh pressure heat-treated Mg-Li-Y alloys. (15th August 2020) - Zhang, Shun; Sun, Yong; Wu, Ruizhi; Wang, Xiang; Chen, Xiao-Bo; Fernandez, Carlos; Peng, Qiuming
Abstract: Achieving good strength-ductility of Mg alloys has always been a crucial issue for the widespread applications of Mg-based structural materials. Herein, an unexpected double-stage strengthening phenomenon was discovered in Mg-8Li-1Y(wt.%) alloys through high pressure (6 GPa) heat treatments over a range of 700-1300 °C. Attractively, the yield strength values are improved remarkably without losing their ductility. The low temperature strengthening mechanism is mainly driven by the formation of large-volume nanoscale contraction twins. In contrast, the high-temperature strengthening reason is ascribed to the presence of densely nano-sized stacking faults. Both coherent interfaces contribute effectively to high mechanical strength without any tradeoff in ductility.